Caring for caregivers after a stroke. (10th November 2014) - Ski, Chantal F.; Castle, David J.; Lautenschlager, Nicola T.; Moore, Gaye; Thompson, David R.
Abstract : Stroke usually occurs in the latter years of life, is sudden and all too often unexpected and unforgiving. When non-fatal, stroke, the second leading cause of disability after dementia, is nearly always disabling (World Health Organization (WHO), 2011 ). Due to common ensuing physical and cognitive impairments, many stroke survivors are unable to care for themselves in the following weeks, months, and possibly years (Lutz et al., 2011 ). Thus, the caregiver role is instant and often long-term with no or very little time to adapt to the many, varied and immediate challenges.